WebCaL – A Domain Specific Language for Web Caching - Gulwani, Sumit; Tarachandani, Asha; Gupta, Deepak; Sanghi, Dheeraj, Luciano Porto Barreto; Consel, Charles, Gilles Muller (Computer Communications, 2000)
Web Caching aims to improve the performance of the Internet in three ways - by improving client latency, alleviating network traffic and reducing server load. A web cache is basically a limited store of information which helps in presenting a faster web access environment to the clients. The performance of a cache depends on proper management of this information and effective inter-cache communication. The existing web caches have simple and hard-coded policies which are not best suited for all environments. They offer limited flexibility and that too just in the form of changing some simple parameters such as cache size, peer caches etc. This drawback motivates the need for a framework for building new web caches tailored to specific environments. In this paper, we describe a Domain Specific Language based on an event-action model using which new local web cache policies and inter-cache protocols can be easily specified. This should make it possible to write a new policy or protocol quickly, evaluate its performance and test it thoroughly using the complete program-execute-debug cycle.